Influence of the Electric Field on the Properties of Hydrogenated Graphene - V. V. Muravyov; V. N. Mishchenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Graphene is currently considered as one of the most promising materials for the creation of new semiconductor devices for various frequency ranges. The influence of an external electric field on the properties of the band diagram of the graphene material, which is a modification of graphene using hydrogen atoms, was studied by simulating from the first principles (ab initio method). It was found that an external electric field applied to the graphene structure leads to a substantial change in its band diagrams, which is associated with a change in their type. At small values of external electric field strength, approximately up to 0.3 a.u. (1 a.u. ≈ 51.4 1010 V/m), we observe graphane zone diagrams with straight minimal gap for Г valley between conduction and valence zones. With further increase in external electric field strength the zone diagrams show indirect minimal gap. With even higher values of external electric field strength, which exceed 0.8 a.u., graphane band diagrams take on a form peculiar to metallic structures. These dependences and the resulting graphene parameters could be the basis for new heterostructure devices containing layers of graphene and other semiconductor materials.